2020
DOI: 10.1248/bpb.b19-00510
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin-9 Peptide Enhances Memory and Ameliorates Aβ<sub>1–42</sub>-Induced Object Memory Impairment in Mice

Abstract: Accumulating evidence suggests that the inhibition of neuroinflammation is a potential target for therapeutic or preventive strategies for Alzheimer's disease (AD). Chemerin has attracted particular attention for its role in the regulation of inflammation. In addition, amyloid β 1-42 (Aβ 1-42) can interact with chemokine-like receptor 1 (CMKLR1), the receptor for chemerin, and induce microglial chemotaxis. Meanwhile, CMKLR1 is expressed in the brain, and both chemerin and Aβ 1-42 share the same receptor. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…For example, vWAT contains plenty of adipocytes that are capable to secrete multiple hormones. Many of these hormones have been proved to participate in the pathogenesis of AD ( Table 1 ), including metabolism of Aβ, 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 phosphorylation of tau, 182 , 183 , 189 , 191 , 192 hippocampal neurogenesis, 181 , 193 , 194 neurodegeneration, 181 , 195 synaptic function, 196 , 197 , 198 , 199 , 200 neuroinflammation 186 , 201 , 202 , 203 , 204 , 205 , 206 and oxidative stress. 181 , 182 , 184 , 206 , 207 , 208 All the findings indicate the vWAT-derived hormones could be a mediator between vWAT and AD.…”
Section: Potential Involvement Of Brain-visceral White Adipose Tissue...mentioning
confidence: 99%
“…For example, vWAT contains plenty of adipocytes that are capable to secrete multiple hormones. Many of these hormones have been proved to participate in the pathogenesis of AD ( Table 1 ), including metabolism of Aβ, 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 phosphorylation of tau, 182 , 183 , 189 , 191 , 192 hippocampal neurogenesis, 181 , 193 , 194 neurodegeneration, 181 , 195 synaptic function, 196 , 197 , 198 , 199 , 200 neuroinflammation 186 , 201 , 202 , 203 , 204 , 205 , 206 and oxidative stress. 181 , 182 , 184 , 206 , 207 , 208 All the findings indicate the vWAT-derived hormones could be a mediator between vWAT and AD.…”
Section: Potential Involvement Of Brain-visceral White Adipose Tissue...mentioning
confidence: 99%
“…Chemerin-9, an analog of chemerin, has a higher affinity for CMKLR1 and functions as an anti-inflammatory regulator to inhibit the development of atherosclerosis, Alzheimer's disease, and pancreatogenic diabetes [22][23][24]. However, the role of chemerin-9 in the biological behavior of AAA has so far been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Chemerin-9 (149-157), comprising nine amino acids from the C-terminus of chemerin, retains most agonist activity [22]. In vivo, chemerin-9 exerts an anti-inflammatory effect by targeting CMKLR1, thus restraining the development of several diseases, including atherosclerosis, Alzheimer's disease, and pancreatogenic diabetes [22][23][24]. However, the role of chemerin-9 in AAA behavior has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In support, central administration of the nonapeptide chemerin-9, derived from the C-terminus of the chemerin precursor, enhances cognition and memory performance. Additionally, chemerin-9 protects against neuroinflammation caused by amyloid-β and memory impairment caused by Aβ42 ( Lei et al, 2020 ). Furthermore, in a mouse model of Alzheimer’s CMKLR1 deficiency improves cognitive deficits ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that high-fat feeding increases circulating levels of chemerin, induces inflammatory markers and results in a decline of cognitive performance ( Helfer and Wu 2018 ; Tan and Norhaizan 2019 ; Léniz et al, 2022 ) and recent studies have implicated the chemerin-CMKLR1 axis in cognitive function ( Lei et al, 2020 ; Zhang et al, 2020 ), in this study we aimed to test the link between the hypothalamic chemerin-CMKLR1 pathway, neuroinflammation and cognition after high-fat feeding. We used a combination of pharmacological and genetic manipulation approaches to block CMKLR1 signaling in the hypothalamus and showed that modulating chemerin function has a profound effect on body weight of high-fat fed rats acutely and chronically.…”
Section: Introductionmentioning
confidence: 99%